Recurrent seizure‐related GRIN1 variant: Molecular mechanism and targeted therapy - Yuchen Xu; Rui Song; Wenjuan Chen; Katie Strong; Daniel Shrey; Satyanarayana Gedela; Stephen F. Traynelis; Guojun Zhang; Hongjie Yuan (Annals of Clinical and Translational Neurology, 2021)
Abstract Objective Genetic variants in the GRIN genes that encode N‐methyl‐D‐aspartate receptor (NMDAR) subunits have been identified in various neurodevelopmental disorders, including epilepsy. We identified a GRIN1 variant from an individual with early‐onset epileptic encephalopathy, evaluated functional changes to NMDAR properties caused by the variant, and screened FDA‐approved therapeutic compounds as potential treatments for the patient. Methods Whole exome sequencing identified a missense variant in GRIN1. Electrophysiological recordings were made from Xenopus oocytes and transfected HEK cells to determine the NMDAR biophysical properties as well as the sensitivity to agonists and FDA‐approved drugs that inhibit NMDARs. A beta‐lactamase reporter assay in transfected HEK cells evaluated the effects of the variant on the NMDAR surface expression. Results A recurrent de novo missense variant in GRIN1 (c.1923G>A, p.Met641Ile), which encodes the GluN1 subunit, was identified in a pediatric patient with drug‐resistant seizures and early‐onset epileptic encephalopathy. In vitro analysis indicates that GluN1‐M641I containing NMDARs showed enhanced agonist potency and reduced Mg2+ block, which may be associated with the patient’s phenotype. Results from screening FDA‐approved drugs suggested that GluN1‐M641I containing NMDARs are more sensitive to the NMDAR channel blockers memantine, ketamine, and dextromethorphan compared to the wild‐type receptors. The addition of memantine to the seizure treatment regimen significantly reduced the patient’s seizure burden. Interpretation Our finding contributes to the understanding of the phenotype–genotype correlations of patients with GRIN1 gene variants, provides a molecular mechanism underlying the actions of this variant, and explores therapeutic strategies for treating GRIN1‐related neurological conditions.